LEGAL PROTECTION OF CHILDREN AS VICTIMS OF HUMAN TRAFFICKING BASED ON JUSTICE VALUE - Anis Mashdurohatun; Wa Ode Khatija Rasia (Jurnal Pembaharuan Hukum, 2017)
The purpose of this study is to examine and analyze f actor Factors affecting the legal protection of children as victims of human trafficking and formulating legal protection based on values of justice.Method The approach used in this study is normative, where the source data comes from secondary data, which consists of primary legal materials, secondary and tertiary. The results found that thefactors that most influence the occurrence of the crime of trafficking of children is a factor of economic and cultural factors. P potential protective laws against child as a victim of human trafficking based on values of justice, in a preventive form a variety of legislation, cooperation and coordination between state agencies, international cooperation and conduct socialization to the public about the dangers of human trafficking crimes. And repressively impose sanctions that are oriented to the victim.